2015
DOI: 10.1093/hmg/ddv288
|View full text |Cite
|
Sign up to set email alerts
|

Muscle hypertrophy induced by myostatin inhibition accelerates degeneration in dysferlinopathy

Abstract: Myostatin is a secreted signaling molecule that normally acts to limit muscle growth. As a result, there is extensive effort directed at developing drugs capable of targeting myostatin to treat patients with muscle loss. One potential concern with this therapeutic approach in patients with muscle degenerative diseases like muscular dystrophy is that inducing hypertrophy may increase stress on dystrophic fibers, thereby accelerating disease progression. To investigate this possibility, we examined the effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 30 publications
1
42
2
Order By: Relevance
“…When challenged with genetic gain of follistatin expression, a prohypertrophic manipulation, Dysf-null muscles showed exacerbation of muscle degeneration. 58 More refined studies, especially with treatment duration >4 weeks, are required to shed light on the interplays between intermittent steroid dosing and muscle mass remodeling pathways. However, these data support further investigation into mechanisms and biomarkers of these divergent steroid effects so that these preclinical findings can be translated into humans with muscle disease.…”
Section: Daily Prednisone Promoted Marked Adipogenesis In Dysferlin-dmentioning
confidence: 99%
“…When challenged with genetic gain of follistatin expression, a prohypertrophic manipulation, Dysf-null muscles showed exacerbation of muscle degeneration. 58 More refined studies, especially with treatment duration >4 weeks, are required to shed light on the interplays between intermittent steroid dosing and muscle mass remodeling pathways. However, these data support further investigation into mechanisms and biomarkers of these divergent steroid effects so that these preclinical findings can be translated into humans with muscle disease.…”
Section: Daily Prednisone Promoted Marked Adipogenesis In Dysferlin-dmentioning
confidence: 99%
“…Another important finding in the present study is the increased follistatin mRNA levels after AET. Previous studies have demonstrated a significant relationship between follistatin and muscle growth and/or hypertrophy . Actually, Sun et al .…”
Section: Discussionmentioning
confidence: 99%
“…At 5 days, myotubes were exposed to different Folfiri (50 μg/ml 5-FU, 10 μg/ml Leucovorin, 20 μg/ml CPT-11; Sigma Aldrich, St. Louis, MO), in combination with either PD98059 (20 μM; Selleckchem, Houston, TX) or ACVR2B/Fc (10 μg/ml) or for up to 48h. ACVR2B/Fc protein expression from the stable Chinese hamster ovary (CHO) cells was induced with 100 nM Cadmium in serum-free CHO media, and ACVR2B/Fc protein was purified from the conditioned medium using protein A Sepharose, as shown in [64]. CHO-ACVR2B/Fc cells were a kind gift of Dr. See-Jin Lee (Johns Hopkins University, Baltimore, MD).…”
Section: Methodsmentioning
confidence: 99%